Design and testing of two-dimensional particle-image velocimetry system - Chan, Wei Ming. (2013)
Particle-Image Velocimetry (PIV) is a technique for the whole field measurement of fluid flow velocity and other fluid parameters, by capturing the displacement of tracer particles in the fluid between multiple frames of known intervals. PIV is commonly utilized in research and education but should be made more accessible at the academic level. Cost is the limiting factor to doing so. This immediate objective of this project is to design a two-dimensional PIV system using improvised equipment and software. A major part of the project is to interface the separately acquired PCO Pixelfly camera, Quantel EverGreen EVG00145 laser system and the National Instruments CompactDAQ data acquisition system. National Instruments Labview software was selected to send software triggering commands to the CompactDAQ and PIVlab was chosen as the post-processing software. A functional test helps to evaluate the improvised setup with a low-speed fluid motion test case. The setup was able to acquire clear double-frame PIV images with minimal fluctuations in trigger timings. After vector validation in PIVlab, the direction of the vectors obtained was largely consistent with the fluid motion in the test case, which confirmed the feasibility of the setup. In the future, dedicated hardware-based triggering using a synchronizer could be included in the setup to improve timing precision. The test case could be expanded to a larger scale to determine the suitability of the setup for high-speed fluid flow applications.